2014
DOI: 10.1002/mds.26083
|View full text |Cite
|
Sign up to set email alerts
|

Combining cell transplants or gene therapy with deep brain stimulation for Parkinson's disease

Abstract: Cell transplantation and gene therapy each show promise to enhance the treatment of Parkinson's disease (PD). However, because cell transplantation and gene therapy generally require direct delivery to the central nervous system, clinical trial design involves unique scientific, ethical, and financial concerns related to the invasive nature of the procedure. Typically, such biologics have been tested in PD patients who have not received any neurosurgical intervention. Here, we suggest that PD patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Also, some studies have shown that molecules secreted by hMSCs promote nervous tissue regeneration through activation/modulation of endogenous neuro-restorative processes. In the future, such molecules could be an efficacious add-on if combined with cell transplantation, pharmacological or surgical strategies (Buttery and Barker, 2014;Choi et al, 2010;Rowland et al, 2015;Yao et al, 2016). Although most of the available results support hMSCs secretome as a promising cell-free therapy and a potential off-the-shelf product for PD, current sources of MSCs do not allow for the isolation of a sufficient number of cells for their widespread clinical use, instead relying on invasive, expensive and labor-intense isolation protocols that yield MSCs with limited proliferative capacity (Teixeira et al, 2016b).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Also, some studies have shown that molecules secreted by hMSCs promote nervous tissue regeneration through activation/modulation of endogenous neuro-restorative processes. In the future, such molecules could be an efficacious add-on if combined with cell transplantation, pharmacological or surgical strategies (Buttery and Barker, 2014;Choi et al, 2010;Rowland et al, 2015;Yao et al, 2016). Although most of the available results support hMSCs secretome as a promising cell-free therapy and a potential off-the-shelf product for PD, current sources of MSCs do not allow for the isolation of a sufficient number of cells for their widespread clinical use, instead relying on invasive, expensive and labor-intense isolation protocols that yield MSCs with limited proliferative capacity (Teixeira et al, 2016b).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The strategy of combining the delivery of biological therapy with DBS surgery has been recently gaining momentum. 26 DBS therapy alone is insufficient for treating all of the symptoms associated with PD, and so, new therapies need to be developed to enhance the therapeutic benefits of DBS. The combined strategy outlined here presents one means of fulfilling this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Third, DBS therapy was amenable to testing the effects of an intervention on the baseline components of PD. Although this approach has been proposed previously for investigating a gene therapy approach, 7,26 it was not actually performed. Thus we report the first clinical study to involve the investigation of a surgical therapeutic intervention in combination with DBS therapy.…”
mentioning
confidence: 99%
“…While DBS in itself may be one of the most exciting and intriguing recent achievements in the treatment of brain disorders, the surgical procedure inevitably required, might in itself facilitate trials of experimental biologic approaches that require co-administration of a gene, growth factor or cell therapy being directly delivered to the central nervous system [109]. Many of the patients meeting inclusion criteria for DBS trials would also be suitable for such biological trials.…”
Section: Future Directionsmentioning
confidence: 98%